Guideline gynekologických zhoubných nádoruů I. Standard--komplexní lécba ovariálních epiteliálních zhoubných nádorů - Robová, H; Rob, L; Svoboda, B; Fínek, J; Safár, P; Spacek, J; Petruzelka, L; Chovanec, J; Oncogynecology Section of the Czech Gynecology and Obstetrical Society (Ceska gynekologie, 2006)
OBJECTIVE: Elaboration of guideline for primary and secondary treatment of ovarian cancer. DESIGN: Review, consensus between proposers and opponents. METHOD: A retrospective review of published data, analysis of Czech statistics and consensus between proposers and opponents. RESULTS: We underline importance of comprehensive approach in therapy of ovarian cancer. We notice importance of expert ultrasound and CA 125 level in diagnostic algorithm. Extension of surgery depends on result of frozen section. All departments which want to perform surgery for ovarian resistance must have possibility to do peroperative histopathology. We can perform conservative fertility sparing surgery in patient with wishing of pregnancy and low stage disease. The effort of maximal debulking with radical surgery including lymphadenectomy is the standard procedure. When we diagnose ovarian cancer during laparoscopy, we have to convert on laparotomy procedure. We define the role of the neoadjuvant chemotherapy followed by surgery after 3-4 cycles of chemotherapy. We define adequate surgery treatment, indication for adjuvant chemotherapy and indication for second line therapy. CONCLUSION: Guideline for the treatment of epithelial ovarian cancer should become directions for clinicians and others, who participate in the process of treatment of the ovarian cancer. The guidelines include all parts of the process from diagnosis, treatment to follow up. All topics of the guidelines arose from a voting of the proposers and opponents.
Keywords: Carcinoma; ženské pohlaví; Humans; nádory vaječníků; Female; Ovarian Neoplasms; lidé; karcinom